Incidencia de los juegos recreativos en el desarrollo del pensamiento lógico de los estudiantes del segundo año de educación básica de la Escuela 12 de Octubre del Reciento La Legua, Parroquia Pimocha, del Cantón Babahoyo, Provincia Los Ríos - Huacon Diaz, Liliana Rossana (2020)
This project is about the methods of teaching methodology, so that through this the students have a better learning, therefore, it is specified that the game is one of the most interesting and least tedious methodologies that teachers can use to that our students remain active and not distracted, they are also better interested in classes. Using the game strategy helps the child relax in classes, and have a greater emotional bond with his classmates and teachers which will help him improve his learning. In addition, it facilitates the logical development from the first years of study of a child, giving openness in all areas of knowledge, since with the strategy of the game they would like it. I also suggest it as a very good strategy to be applied in all areas, because it will help us with our class development so that the student loses the fear of participation, integration and the classes themselves.